A comparative study of Widal test with blood culture in the diagnosis of typhoid fever in febrile patients (Journal of Dhaka National Medical College & Hospital, 2022)
Background: Typhoid fever is a major health problem in developing countries and its diagnosis on clinical ground is difficult. Diagnosis in developing countries including Bangladesh is mostly done by Widal test. However, the value of the test has been debated. Hence, evaluating the result of this test is necessary for correct interpretation of the result. Objective of the study was to compare the result of Widal test with Blood Culture in the diagnosis of typhoid fever in febrile patients in Dhaka National Medical Institute Hospital.Methods: Blood samples were collected from 270 febrile patients with symptoms clinically similar to typhoid fever and visiting Dhaka National Institute Hospital from December 2015 to April 2016. Blood culture was used to isolate S.typhi andS.paratyphi. Slide agglutination test and tube agglutination tests were used for the determination of antibody titer. An antibody titer of ≥1:80 for anti TO was taken as a cut of value to indicate recent infection of typhoid fever.Results: One hundred and eighty six (68.9%) participants were females and eighty four (31.1%) were males. 7 (2.6%) cases of S. typhiand 4 (1.5%) cases of S. paratyphi were identified with the total prevalence of typhoid fever 4.1%. The total number of patients who have indicative of recent infection by O antigen is 160 (59.2%). The sensitivity, specificity, positive predictive value(PPV) and negative predictive value(NPV) of Widal test were 71.4%, 41.06%, 3.1% and 98.1% respectively. Conclusions: Widal test has a low sensitivity, specificity and PPV, but it has good NPV which indicates that negative Widal test result have a good indication for the absence of the disease.J. Dhaka National Med. Coll. Hos. 2022; 28 (01): 10-15